Expression and activity of oxidative stress enzymes in mediatiing fluconazole resistance in candida albicans and their regulation by berbine - Poopedi, Evida (My University, 2019)
Introduction Despite the availability of several antifungal drugs, Candida infections remain a major health threat worldwide. The Candida infections problem has been amplified by the emergence of multidrug resistant Candida species towards the conventional antifungal drugs. In addition, activation of antioxidant defense system by Candida species has been known to be forefront mechanism to escape drug toxicity.This indicates an urgent need for the development of new therapeutic strategies and antifungal drugs. Natural products have served for centuries for the treatment of infectious diseases and are among the major sources for finding new antifungal drugs. Berberine (BER), an isoquinoline alkaloid found in a variety of plant species, has been shown to possess multiple biological and pharmacological properties including antimicrobial activity against C. albicans and other Candida species. However, the mechanism of action exerted by BER and its effect on Candida cells is not yet fully elucidated. Therefore, this study was conducted to evaluate the role of antioxidant enzymes in the susceptibility to fluconazole (FLC) in C. albicans. Another aspect was to determine the effect of BER on growth, antioxidant enzymes and their gene expression in C. albicans. Materials and methods Candida albicans clinical isolates (10 FLC susceptible and 10 FLC resistant) and one ATCC strain were obtained from the Department of Clinical Microbiology and Infectious Diseases, University of the Witwatersrand. Species identification was confirmed using API 20C AUX. Antifungal susceptibility was determined following CLSI M27-A3 guidelines. Gene expression of SOD1, SOD2, GPx2, GLR1, GTT11, and CAT1 in untreated and BER treated C. albicans cells was measured by RT-qPCR. The activity level of the corresponding enzymes in the presence of BER was determined using a spectrophotometer. Results Gene expression analysis showed an increase in mRNA expression level of SOD1, SOD2, GPx2, GLR1 and GTT11 genes in FLC resistant isolates than in the susceptible group. The most significantly expressed gene was SOD1 with 50.69-fold increase. The other genes showed moderate increase in the expression with fold change ranging from 1.2 to 4.2. The susceptibility test showed MICs ranging from 125 to 500 μg/ml with a significant difference in the activity of BER between FLC susceptible and resistant C. albicans. BER treatment induced upregulation in the mRNA expression and enzymatic activities of major antioxidants. In FLC resistant C. albicans, treatment with ½ MIC value of BER caused downregulation of the targeted antioxidant genes indicating that BER at this concentration induced an intense oxidative stress, therefore, surpassing the antioxidant capacity of the cells. Conclusion The findings in this study showed that drug resistance is not only caused by mutations in a particular gene but could also arise from proteomic modulations. The study . The study also demonstrated that C. albicans activates several antioxidant enzymes that form an integral component of the cell’s response against oxidative stress. Candida albicans showed efficient antioxidant response at lower concentrations of BER. However, BER at ½ MIC value induced robust oxidative stress, especially in FLC resistant C. albicans, surpassing the antioxidant capacity of the cells. This demonstrates that BER at sub-inhibitory concentrations is able to render C. albicans avirulent by suppressing its antioxidant defense response without compromising cell viability of the fungi. Therefore, BER has a potential to be developed into BER has a potential to be developed into a therapeutic agent a therapeutic agent for for the the treatment oftreatment of C. albicansC. albicans infections and other pathogenic fungi to infections and other pathogenic fungi to overcome drug resistance. overcome drug resistance.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine.
Keywords: Candida albicans--diet therapy; Diet therapy